PS 11-74 PREHYPERTENSION IS ASSOCIATED WITH EARLY COMPLICATIONS OF ATHEROSCLEROSIS, BUT NOT WITH THE EXERCISE CAPACITY. (September 2016) - Jung, Mi-Hyang; Ihm, Sang-Hyun; Lee, Dong-Hyeon; Park, Ha-Wook; Chung, Woo-Baek; Jung, Hae Ok; Youn, Ho-Joong
Abstract : Objective: Prehypertension is highly prevalent and associated with the risk of progression to overt hypertension. Nevertheless, little attention has been paid to the subjects of this category. This study aimed to evaluate the association between prehypertension with subclinical end-organ damage and the exercise capacity. Design and Method: From January 2011 to May 2013, we enrolled 447 asymptomatic participants with blood pressure (BP) <140/90 mmHg who underwent comprehensive health check-ups at tertiary hospital. Those who had antihypertensive medications (n = 65) were excluded. A total of 382 participants (mean age 53 ± 9 years, females 36.9%) were entered into the final analysis and categorized into two groups: optimal BP (systolic BP < 120 mmHg and diastolic BP < 80 mmHg, n = 173) and prehypertension (120 ⩽ systolic BP < 140 mmHg and/or 80 ⩽ diastolic BP < 89 mmHg, n = 209). Results: Participants with prehypertension exhibited more obese features (body mass index, 25.1 ± 3.7 vs. 24.3 ± 3.6 kg/m 2 ; abdominal circumference, 87.4 ± 12.1 vs. 82.8 ± 9.7 cm; and fat mass, 19.3 ± 6.1 vs. 16.7 ± 4.8 g; all p<0.001). The laboratory findings demonstrated higher levels of the fasting glucose (103.8 ± 26.0 vs. 97.2 ± 21.6 mg/dL, p = 0.007), HOMA-IR (1.18 ± 0.87 vs. 0.87 ± 0.55, p < 0.001), uric acid (6.0 ± 1.4 vs. 5.4 ± 1.3 mg/dL, p < 0.001), and triglycerides (123.1 ± 87.9 vs. 101.3 ± 59.7 mg/dL, p = 0.005) in the prehypertensive participants. They also had a higher LV mass index (84.5 ± 16.7 vs. 76.2 ± 14.4 g/m 2, p < 0.001) and E/e', and lower LV ejection fraction, but the latter two were not statistically significant. Additionally, the pulse wave velocity level was significantly higher for prehypertension (1342.5 ± 458.1 vs. 1223.1 ± 467.7 cm/sec, p = 0.019). However, no significant difference in the exercise capacity was noted between the two groups (peak VO2 ; 28.3 ± 7.7 vs. 27.9 ± 6.9 mL/kg/min, p = 0.616). Conclusions: Our observations demonstrated that prehypertension was associated with a metabolic disorder and subclinical end-organ damage, but not with the exercise capacity.